The application of manufacturing audits to identify and analyze production strategies: study carried out in a small graphics company - Thesari, Shirley Suellen; Tonello, Renato; Trojan, Flavio; Lizot, Lizot (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose - This study intends to identify, analyze and formulate manufacturing strategies for small companies. The application of management methodologies on manufacturing processes in small companies is not commonly adopted, since an immediate return is not generated, and when it is compared to the effort required to understand and apply it. Design/methodology/approach – An adaption to a manufacturing audit methodology was used, illustrated by using the application to a small printing company. Findings - The situation that occurs frequently in small and family-owned enterprises, where even making activities more professional is not considered relevant, and seen as a waste of time and money, can certainly be improved using manufacturing audits. However, with technological advances, even small companies need to develop and reflect on manufacturing strategies to remain in the market. Originality/value - This approach becomes efficient when it focuses and analyzes these strategies, which are usually unclear for small companies, identifying weaknesses and opportunities for improvement to leverage the competitiveness of these companies, by defining more effective strategies. In addition, the study contributes theoretically when it seeks to adjust a methodology that has already been consolidated in large corporations, and which needs to be adapted to the reality of the scenario presented. Keywords - Manufacturing strategy, auditing, printing industry.